The Role of Satisfaction Information and Service Quality as a Communication Media Base to Increase Loyalty - Sri Wahyuningsih; Zaharudin Zaharudin; Harries Madiistriyatno; Yan Ariyanto (International Journal of Artificial Intelligence Research, 2022)
This study aims to analyze the influence of service quality information and customer satisfaction information on customer loyalty at PT Mulia Keramik Indah Raya Jakarta. The research method is a quantitative method with primary and secondary data. The sampling technique uses the probability sampling method. The data analysis technique is multiple linear regression. The results showed that the service quality information variables and customer satisfaction information partially affected customer loyalty at PT Mulia Keramik. The coefficient of determination shows 75.2%, this indicates that the variation in the information variable on service quality and customer satisfaction information is able to explain the variation in the ups and downs of the customer loyalty variable by 75.2% while the remaining 24.8% is influenced by other variables outside this study, such as : price, location, product quality.